Quantum effects dominating the interatomic coulombic decay of an extreme system - Ben-Asher, Anael; Landau, Arik; Cederbaum, Lorenz S.; Moiseyev, Nimrod (The journal of physical chemistry letters, 2020)
LiHe is an extreme open-shell system. It is among the weakest bound systems known, and its mean interatomic distance extends dramatically into the classical forbidden region. Upon 1s → 2p excitation of He, interatomic Coulombic decay (ICD) takes place in which the electronically excited helium atom relaxes and transfers its excess energy to ionize the neighboring lithium atom. A substantial part of the decay is found to be to the dissociation continuum producing Li+ and He atoms. The distribution of the kinetic energy released by the ICD products is found to be highly oscillatory. Its analysis reveals that quantum phase shifts between the decaying states and the dissociating final states are controlling this ICD reaction. The semiclassical reflection principle, which commonly explains ICD reactions, fails. The process is expected to be amenable to experiment.
Gesehen am 05.10.2020